ADAPTING THE OLDENBURG BURNOUT INVENTORY INTO BAHASA INDONESIA FOR MEASURING BURNOUT IN MEDICAL RESIDENTS - Annang Giri Moelyo; Muchtar Hanafi (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2022)
Background: Burnout is common among medical residents, and a non-commercial tool for assessing burnout for medical residents is needed. This study aimed to adapt the Oldenburg Burnout Inventory (OLBI) in Bahasa Indonesia for medical residents and to analyze its validity and reliability.Case Discussion: The English version of OLBI was forward and backward translated to and from Bahasa Indonesia by English-language translation experts, and was appropriately modified by the authors. The respondents of the questionnaire were taken from pediatric residents in the first trial (48 subjects), and from internal medicine, pediatric, dermatology, surgery, and neurology residents in the second trial (109 subjects). The item-test correlation to measured construct validity was good for both trials. A confirmatory factor analysis was then undertaken to evaluate the goodness of fit (GOF), the root mean squared error of approximation (RMSEA), comparative fit index (CFI), Tucker-Lewis index (TLI), standardized root mean squared residual (SRMR), and coefficient of determination (CD) in the second trial. The results of the one-factor model and multidimensional GOF of the 16 items were unsatisfactory (χ2<0.05 and RMSEA>0.08). The GOF of the two-factor analysis of burnout with 8 items (3 exhaustion items and 5 disengagement items) created the following results: χ2=0.378; RMSEA=0.025; CFI=0.995; TLI=0.993; SRMR=0.036; and CD=0.898. The Cronbach’s alphas, for internal consistency reliability, in the first trial, second trial, and final model were 0.73, 0.87, 0.83, and 0.79, respectively.Conclusion: An 8-items modified Bahasa Indonesia translation of the OLBI for medical residents to measure burnout has good reliability and validity.